2014
DOI: 10.1097/prs.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of Skin Viability Using Visible Diffuse Reflectance Spectroscopy and Autofluorescence Spectroscopy

Abstract: These findings will be helpful to clinicians for making a precise judgment on flap viability. Furthermore, the authors' results highlight the advantage of using autofluorescence spectroscopy in the early prediction of skin flap viability relative to diffuse reflectance spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
(23 reference statements)
1
8
0
1
Order By: Relevance
“…From Table 1 to and Figure , it can be found that the autofluorescence imaging always yields better performance compared to diffuse reflectance imaging. The better performance of autofluorescence imaging compared with diffuse reflectance imaging in the classification between the control group and the occluded group in Table agrees with our earlier flap viability study [22], likely because autofluorescence measurements offers an advantage for detecting tissue ischemia . In contrast, the worse performance of diffuse reflectance imaging in Table 1 to and Figure disagrees with the results in our parallel point measurement study .…”
Section: Discussionsupporting
confidence: 63%
“…From Table 1 to and Figure , it can be found that the autofluorescence imaging always yields better performance compared to diffuse reflectance imaging. The better performance of autofluorescence imaging compared with diffuse reflectance imaging in the classification between the control group and the occluded group in Table agrees with our earlier flap viability study [22], likely because autofluorescence measurements offers an advantage for detecting tissue ischemia . In contrast, the worse performance of diffuse reflectance imaging in Table 1 to and Figure disagrees with the results in our parallel point measurement study .…”
Section: Discussionsupporting
confidence: 63%
“…Fluorescence spectroscopy utilizing exogenous [12] and endogenous fluorophores [13][14][15][16] to measure the metabolic rate of tissue has been reported in recent years, which could compensate for the weakness of those methods measuring the peripheral information of flap perfusion. Previously we evaluated both visible diffuse reflectance and auto-fluorescence spectroscopy to identify their values for the early prediction of skin flap viability in a MacFarlane rat dorsal skin flap model [17], our results show that either visible diffuse reflectance spectroscopy or autofluorescence spectroscopy alone can predict skin viability accurately and the combination of the two yields the highest accuracy for early prediction in the first 15 minutes.…”
Section: Introductionmentioning
confidence: 89%
“…Our works are focused on the combination of steady-state and spatially resolved Diffuse Reflectance (DR) spectroscopy and multiple excitation AutoFluorescence (AF) spectroscopy to improve diagnosis efficiency of skin precancerous tissues 1,10,11 . For simplicity and cost effective instrumentation considerations, steadystate excitation and spatial resolution are preferred 16 .…”
Section: Introductionmentioning
confidence: 99%